TEACHING AND LEARNING ENGLISH PARADIGM AND THE IMPLEMENTATION OF THE POLICY - Zainal ‘Arifin (Register Journal, 2015)
Theory on Teaching English is currently moving on a paradigm shift. This paradigm occurred because of a review on the basics of linguistic, pedagogic and the review on the impact of sociolinguistics in a globalized setting. This paper aims to show the results of comparative study which is textual on the teaching and learning English paradigm and the policy has been implemented by both universities. The objective of the study is to describe the comparison of the paradigm between English Language Education and academic policy in both universities. Descriptive qualitative in the form of textual analysis is used in this study. Data were taken from the analysis of documents and interviews with academicians in both universities then analyzed using the theory of a paradigm shift in learning English (Kostoulas, 2010) and academic policy (Center for Quality Assurance, UGM, 2012) using an interactive model of Miles and Huberman. The validity of the data used triangulation methods and data sources. The results show that the content of English Language Education taught at the Division of English Language Education (ELE) HKU and at the English Language Education Department (PBI) IAIN Surakarta have the same characteristics but the ways in providing educational materials are relatively different. The paradigm and academic policiy in ELE HKU applied the learning paradigm while at PBI IAIN Surakarta is still applying on teaching paradigm. When the study was conducted by researcher, the ELE Department IAIN Surakarta has been moving towards a paradigm shift in some academic elements as the use of the methods by lecturers called learning paradigm, although the method is not covered by the policy. The difference between Paradigm and policy in both universities is influenced by the context of the political situation, especially the rules of ministry of higher education, cultural context and the orientation on each university. Keywords: Paradigm Shift, Academic Policy, English Language Education, Intertextual Analysis